PENGARUH FAKTOR IKLIM TERHADAP POLA SEBARAN INTEGRAL KONSENTRASI KONTAMINAN RADIOAKTIF TAHUNAN DARI CEROBONG REAKTOR KARTINI YOGYAKARTA KE UDARA LINGKUNGAN SEKITARNYA - Mondjo, Mondjo; Sudibyakto, Sudibyakto (Jurnal Sains & Teknologi Modifikasi Cuaca, 2000)
This research is to study the impact of climate factors and environmental risk due tooperation of The Nuclear Reactor of Kartini that is proportional to the annual integratedconcentration of the radioactive contaminant into the air of surrounding areas A research has been done to design a mathematical model to relate the annual integrated concentration of the radioactive contaminant with the radioactive contaminant released from the Reactor of Kartini (the rate the effluents are released, type of the radioactive contaminant, dimension of stack), and climatological factor (wind direction, wind speed, solar radiation percentage) . The result shown that the maximum of annual integrated concentration of the radioactive contaminant of Argon-41 had been on the decrease but variation of the annual climatological factor was not significant with the distribution of it. The map of the annual integrated concentration of Argon-41 shown up the maximum of 3 the annual integrated concentration of Argon-41 was 0,6 ? Ci/m . The area where had the 3 value of the annual integrated concentration of Argon-41 of 0,4 ? 0,6 ? Ci/m (equal to the -5 3mean concentration of Argon-41 of 4,04 ? 6,06 × 10 ? Ci/m ) for the direction of 60° onthe distance of 200 ? 1075 m, the direction of 30° on the distance of 200 ? 800 m, and the direction of 90° on the distance of 300 ? 575 m. The contribution of contaminant released from the stack of the Reactor of Kartini was lower than the natural radioactivity so the operation of the Reactor of Kartini was not significant with the degree of theenvironmental radioactivity.